The Associate Committees on Medical Research of the National Research Council and the Second World War - Romano, Terrie (Scientia Canadensis, 1991)
AbstractDuring World War II the original Associate Committee on Medical Research and three additional committees (each associated with a branch of the military) of the National Research Council organized wartime medical research. The war provided an opportunity for the NRC to demonstrate the utility of medical research and the ability of Canadians to make significant contributions to the allied research effort.